Dual RNA-Seq of H5N1 Avian Influenza Virus and Host Cell Transcriptomes Reveals Novel Insights Into Host-Pathogen Cross Talk - Wang, Qiao; Wang, Zixuan; Zhang, Jin; Zhang, Qi; Zheng, Maiqing; Wen, Jie; Zhao, Guiping; Li, Qinghe (Frontiers in Microbiology, 2022)
H5N1 avian influenza virus (AIV) is a highly pathogenic influenza virus that poses a substantial threat to poultry production and public health. A comprehensive understanding of host–pathogen interactions for AIV requires knowledge of gene expression changes in both the pathogen and the host upon infection. We report the use of dual RNA sequencing technology to uncover trends in gene expression in H5N1 AIV and chickens (DF1 cells) during the course of infection. The expression of all viral genes increased continuously from 0 to 20 hours post infection. We also identified 2,762 differentially expressed host genes during infection. Pathway analysis found that genes related to the signaling pathways of DNA replication, T cell activation, NF-kappa B signaling pathway, and RNA degradation were significantly enriched. We demonstrated that the cis-acting lncRNA MSTRG.14019.1 targeted CSE1L and may affect virus replication. This study provides a more comprehensive and detailed understanding of host-virus interactions at the RNA level during the course of H5N1 AIV infection.